Disequilibrium of crisis - Szymański, Wojciech (Hybris, 2018)
In the time of the European crisis, I find actions motivated by excessive attention paid to the financial and economic matters in analysing its reasons and the search for ways of amending it largely insufficient. Moreover, I believe it is dangerous to neglect the well-being of citizens understood more broadly than just a deficit of financial resources. In this paper, basing on research into finding correlates of subjective well-being of individuals, believing that they are the most effective measure of the quality of policies of any given government, I want to show an alternative approach to the current mainstream theories of happiness. I present a comparison of two dominant indexes used for measuring the quality of governance (IEF - Index of Economic Freedom and GCI, Global Competitiveness Index) and juxtapose them with the relatively recently created third index (SDGI, Sustainable Development Goals Index), citing results suggesting a higher explanatory power of the latter in predicting the well-being of individuals. If those results are correct, it seem that the contemporary, deemed by some to be overly reductionist, approach to improving the well-being of individuals is wrong and a different attitude should at least be considered. One of the „different attitudes” is presented in short in the form of a list of goals within the paradigm of sustainable development.